Sepsis Disrupts Mitochondrial Function and Diaphragm Morphology - Oliveira, Thamires Siqueira; Santos, Anderson Teixeira; Andrade, Cherley Borba Vieira; Silva, Johnatas Dutra; Blanco, Natália; Rocha, Nazareth de Novaes; Woyames, Juliana; Silva, Pedro Leme; Rocco, Patricia Rieken Macedo; da-Silva, Wagner Seixas; Ortiga-Carvalho, Tânia Maria; Bloise, Flavia Fonseca (Frontiers in Physiology, 2021)
Background: The diaphragm is the primary muscle of inspiration, and its dysfunction is frequent during sepsis. However, the mechanisms associated with sepsis and diaphragm dysfunction are not well understood. Herein we evaluated the morphophysiological changes of the mitochondrial diaphragm five days after sepsis induction. Methods: Male C57Bl/6 mice were divided into two groups: cecal ligation and puncture (CLP, n=26) and sham-operated (n=19). Mice received antibiotic treatment eight hours after surgery and then every twenty-four hours until five days after surgery when mice were euthanized and the diaphragms were collected. Also, diaphragm function was evaluated in vivo by ultrasound 120 hours after CLP. Tissue fiber profile was evaluated by the expression of myosin heavy chain and SERCA gene by qPCR and myosin protein by western blot. The Myod1 and Myog expression were evaluated by qPCR. Diaphragm ultrastructure was assessed by electron microscopy and mitochondrial physiology was investigated by high-resolution respirometry, western blot and qPCR. Results: CLP mice developed moderated sepsis, with a 74% survivor rate at 120 hours. The diaphragm mass did not change in CLP mice compared to control, but we observed sarcomere disorganization and increased muscle thickness (38%) during inspiration and expiration (21%). Septic diaphragm showed a reduction in fiber myosin type I and IIb mRNA expression by 50%, but an increase in MyHC I and IIb protein levels compared to the sham mice. Total and healthy mitochondria were reduced by 30% in septic mice, which may be associated with a 50% decrease in Ppargc1a (encoding PGC1a) and Opa1 (mitochondria fusion marker) expressions in the septic diaphragm. The small and non-functional OPA1 isoform also increased 70% in the septic diaphragm. These data suggest an imbalance in mitochondria function. Indeed, we observed downregulation of all respiratory chain complexes mRNA expression, decreased complex III and IV protein levels, and reduced oxygen consumption associated with ADP phosphorylation (36%) in CLP mice. Additionally, the septic diaphragm increased proton leak and downregulated Sod2 by 70%. Conclusions: The current model of sepsis induced diaphragm morphology changes, increased mitochondrial damage, and functional impairment. Thus, diaphragm damage during sepsis seems to be associated with mitochondria dysfunction.